2023
DOI: 10.5713/ab.22.0183
|View full text |Cite
|
Sign up to set email alerts
|

Does supplementing laying hen diets with a herb mixture mitigate the negative impacts of excessive inclusion of extruded flaxseed?

Abstract: Objective: This study investigated the effects of extruded flaxseed with and without herbs mixture on egg performance, yolk fatty acids (FAs), lipid components, blood biochemistry, serological enzymes, antioxidants and immune system of Hy-Line W-36 hens for nine weeks.Methods: Two hundred forty laying hens were randomly distributed to eight treatments, resulting in six replicates with five hens. Graded levels of dietary extruded flaxseed (0, 90, 180, and 270 g/kg) with and without herbs mixture (24 g/kg: garli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…The current study demonstrated successful incorporation of long-chain n -3 PUFAs (e.g., ALA, EPA, and DHA) into the egg yolk via dietary FSCM. These results agree with those of previous studies[ 55 , 59 , 67 , 68 ]. Dietary incorporation of 5 or 10% flaxseed meal in laying hen diets increased the egg yolk contents of PUFAs and n -3 PUFAs, whereas those of MUFAs and the n -3: n -6 ratio decreased[ 54 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The current study demonstrated successful incorporation of long-chain n -3 PUFAs (e.g., ALA, EPA, and DHA) into the egg yolk via dietary FSCM. These results agree with those of previous studies[ 55 , 59 , 67 , 68 ]. Dietary incorporation of 5 or 10% flaxseed meal in laying hen diets increased the egg yolk contents of PUFAs and n -3 PUFAs, whereas those of MUFAs and the n -3: n -6 ratio decreased[ 54 ].…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with those of previous studies[ 54 ] with regard to serum triglyceride, total cholesterol, and the HDL-cholesterol:total cholesterol ratio. Moreover, dietary extruded flaxseed at up to 270 g/kg did not significantly affect the serum concentrations of triglycerides and LDL cholesterol[ 55 ]. However, we found that dietary 10% FSCM increased the serum concentration of HDL cholesterol compared with that in the control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Humans are considered potentially pre-diabetic when HbA1c% exceeds 5.7%, and type 2 diabetes is suspected when HbA1c% exceeds 6.5% [ 167 ]. Humans display a normal blood glucose of 100 mg/dL, whereas laying hens display a higher, normal blood glucose of 300 mg/dL [ 168 ]. Despite having high glucose, chickens have a low HbA1c% ranging from less than 1.0% to slightly less than 2.0% [ 85 , 169 ].…”
Section: Discussionmentioning
confidence: 99%